2023
DOI: 10.1093/heapro/daad080
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of a prescription model for accessing nicotine vaping products: an examination of submissions made by self-reported e-cigarette users to an Australian consultation

Abstract: In response to rapid and substantial increases in rates of e-cigarette use among young people, Australia’s Therapeutic Goods Administration (TGA) made changes to the regulations governing nicotine vaping products. As part of the regulatory change process, Australians were invited to comment on the proposed regulations, which featured the introduction of a prescription model for nicotine vaping products. To inform strategies to enhance compliance with the tightened regulations, this study examined submissions m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… 9 17 Communications highlighting the historical mistake of tobacco cigarettes being made consumer products could be used to inform vapers of the risks associated with regulating e-cigarettes in a manner that is consistent with tobacco products. 25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 17 Communications highlighting the historical mistake of tobacco cigarettes being made consumer products could be used to inform vapers of the risks associated with regulating e-cigarettes in a manner that is consistent with tobacco products. 25 …”
Section: Discussionmentioning
confidence: 99%
“…23 24 Consumers of e-cigarettes have also raised concerns about practitioner hesitancy and the impact of this on access. 25 Given the effectiveness of the prescription model is dependent on medical practitioners being open to prescribing e-cigarettes to smokers who wish to quit but have been unable to do so with first-line treatments, it is critical that practitioners are supported in their practice to prescribe nicotine e-cigarette products when use is clinically indicated.…”
Section: Supply Reduction Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed a digital astroturfing campaign by tobacco and vaping companies during consultations on the proposed restrictions on vaping products in Australia. Researchers found that 26% of submissions from consumers contained copy-pasted text from a template provided by an industry-led campaign (Jongenelis et al , 2023). As noted by the authors, using consumers to make submissions on behalf of the industry bypasses formal requirements to disclose conflicts of interest during public consultations.…”
Section: Digital Astroturfing and Ai In Policy Consultation Processesmentioning
confidence: 99%